Meningkatkan Keterampilan Proses Sains pada Asisten Laboratorium Pendidikan Biologi FKIP UNTAD melalui Bimbingan Praktikum Lapangan Ekologi - Suleman, Samsurizal M.; Laenggeng, Abd. Hakim; Sabran, Moh.; Agni, Raya (Jurnal Kreatif Online, 2020)
This study aims to determine the improvement of science process skills of laboratory assistants of Biology Education FKIP UNTAD through ecology field practicum guidance. The research method used in this research was descriptive by using this type of qualitative research. The subjects in this study were 30 laboratory assistants. Increasing science process skills through ecology field practicum activities including work safety indicators in practicum, skills using tools and materials, skills in making observations, ability to apply sampling methods and techniques, ability to analyze and interpret data, and ability to communicate practical results. Data were analyzed to count the Normalized Gain (N-Gain). Based on the Normalized Gain analysis on the six indicators of science process skills, the assistants overall have an average of 0.67 (classified as moderate). Furthermore, based on the hypothesis test, it showed the tcount (8.899) was greater than the ttable value (2.015) so that the H0 hypothesis was rejected, which means that there was an increase in science process skills at the Biology Education Laboratory Assistant FKIP UNTAD through ecology field practicum guidance.